Wound Induced Hair Neogenesis – A Novel Paradigm for Studying Regeneration and Aging - Bhoopalam, Myan; Garza, Luis A.; Reddy, Sashank K. (Frontiers in Cell and Developmental Biology, 2020)
Keywords: wound-induced hair neogenesis1, aging2, hair follicle neogenesis3, hair follicle stem cells4, Wnt5, WIHN6, STAT37, regeneration8.Hair follicles are the signature dermal appendage of mammals. They can be thought of as miniorgans with defined polarity, distinct constituent cell types, dedicated neurovascular supply, and specific stem cell compartments. Strikingly, some mammals show a capacity for adult hair follicle regeneration in a phenomenon known as wound-induced hair neogenesis (WIHN). In WIHN functional hair follicles reemerge during healing of large cutaneous wounds, and they can be counted to provide an index of regeneration. While age-related decline in hair follicle number and cycling are widely appreciated in normal physiology, it is less clear whether hair follicle regeneration also diminishes with age. WIHN provides an extraordinary quantitative system to address questions of mammalian regeneration and aging. Here we review cellular and molecular underpinnings of WIHN, explore known age-related changes to these elements, and present unanswered questions for future exploration.